Low-Technology Industries And Regional Innovation Systems: The Salmon Industry In Chile - Rojo, Mauricio Maldonado; de Noronha, Teresa (Journal of Tourism, Sustainability and Well-being, 2016)
Results show that the worldwide competitiveness of the low-tech Salmon Industry in the Los Lagos region has not developed the principal factors permitting the consolidation of a Regional Innovation System (RIS). On the contrary we identify important gaps in terms of the regional conditions such as “networking”, “knowledge creation and diffusion”, among others, capable to stimulate the innovation behavior of salmon firms.